Assessment of the Integrity and Function of Human Term Placental Explants in Short-Term Culture (2024)
Human placental explants (HPEs) culture has generated significant interest as a valuable in vitro model for studying tissue functions in response to adverse conditions, such as fluctuations in oxygen levels, nutrient availability, exposure to pathogenic microorganisms, and toxic compounds. HPEs offers the advantage of replicating the intricate microenvironment and cell-to-cell communication involved in this critical and transient organ. Although HPEs culture conditions have been extensively discussed, a protocol for assessing the viability and function of HPEs during short-term culture has not been previously outlined. In this study, we have developed a short-term HPEs culture protocol, specifically up to 72 h, and have employed quantitative, semi-quantitative, and qualitative analyses to evaluate tissue viability and function over time. Under our standardized conditions, placental villi explants began to regain their structural properties (the integrity of the trophoblast and villous stroma) and the functionality of the HPEs (production of angiogenic, endocrine, and immunological factors) starting from 48 h of culture. This restoration ensures a suitable environment for several applications. The data presented here can be highly valuable for laboratories aiming to implement an HPEs model, whether in the process of standardization or seeking to enhance and optimize working conditions and timing with placental tissue.